Zakat distribution, education, and real income per capita in Malaysia - Yusoff, Mohammed (2014)
This paper is multidisciplinary in nature concerning with social, economic, and religious variables. The main objective is to determine the impact of zakat distribution and education levels on real income per capita using panel data of the fourteen states of Malaysia. The results of the estimated fixed effect model are quite satisfactory in terms of correct signs, significant of variables and goodness of fit. All the independent variables are significant at 1% level supporting the hypothesis that zakat expenditure or distribution, primary and secondary school education are important determinants of real income per capita in Malaysia. The results also indicate that secondary school enrolment has the highest impact on real income per capita, followed by primary school enrolment, and zakat spending. As policy implications, it is suggested that Muslim nations must improve the efficiency of zakat collection and spend it prudently as laid out in the al-Qur’an and Hadith. Policymakers should also make serious effort to construct better strategies, planning, and effective policy actions to provide conducive environment and infrastructure for the development in education to increase the stock of human capital in accordance to the need of the nations. These should help increase the real income per capita and improve the standard of living of Muslim community.